Réseaux à valeur ajoutée et réassurance : enjeux stratégiques et management des ressources technologiques - Levavasseur, Max (Assurances, 1990)
The author describes the new insurance communication networks RINET (Reinsurance and Insurance Network) and LIMNET (London Insurance Market Network). Designed to promote better ties between insurers throughout the world, these new tools are a boon to their operations and strategies as they may contribute to reducing costs, accelerating electronic exchanges and the decision-making process, facilitating the placement of international risks and improving work methods. These new computerized systems will be developed to an even greater extent in the future. The article provides an overview of the context, how these networks came to be and what is at stake.